Zagadnienie życia i śmierci w powieści "Sanin" Michaiła Arcybaszewa - Witczak, Patryk (Rusycystyczne Studia Literaturoznawcze, 2015)
In this article the author attempts to reinterpret Sanin by Mikhail Artsybashev presenting the novel as philosophical rather than pornographic. The focus here is on the motif of life and death, which occupies a central position in all the works by Artsybashev. The novelist’s understanding of life and death was clearly influenced by the views of German philosophers: A. Schopenhauer and F. Nietzsche. What echoes most vibrantly in the novel are the ideas expounded in Nietzsche’s Thus Spoke Zarathustra, especially the theory of Übermensch, variously translated as “superman” or “overman”.